Comparison of amino acids, biogenic amines and ammonium ion of wines made of different types of fruits. (13th November 2016) - Ouyang, Xiaoyu; Wang, Shaoyang; Yuan, Guanshen; Liu, Yaran; Gu, Pan; Zhang, Bolin; Zhu, Baoqing
Summary: Amino acids, biogenic amines and ammonium ion are the primary nitrogen sources in fruit wines. Compared to grape wines, our knowledge to their profile in wines made of other fruits is very lack. Fourteen wines made of nine kinds of fruits together with seven grape wines were selected to compare their nitrogen component profile. White grape wines possessed the highest level of total amino acids, followed by red grape wines and then the wines made of the other fruits. Red grape wines contained the highest level of biogenic amines, followed by white grape wines and the wines made of the other fruits. Ammonium ion was also found to be higher in the wines made of grapes. Principal component analysis revealed that the obvious separations existed among the wines made from different types of fruits, indicating that these nitrogen compounds could be served as the indicators to differentiate different types of fruit wines. Abstract : The content of amino acids, biogenic amines and ammonium ion varied in commercial wines made of different fruits. And the content of these compounds showed the potential as a tool to separate the wines from different materials.